Small molecules as therapy for uveitis: a selected perspective of new and developing agents. (2nd September 2017) - Pleyer, Uwe; Algharably, Engi Abdel-Hady; Feist, Eugen; Kreutz, Reinhold
ABSTRACT: Introduction : Intraocular inflammation (uveitis) remains a significant burden of legal blindness. Because of its immune mediated and chronic recurrent nature, common therapy includes corticosteroids, disease-modifying anti-rheumatic drugs and more recently biologics as immune modulatory agents. The purpose of this article is to identify the role of new treatment approaches focusing on small molecules as therapeutic option in uveitis. Areas covered : A MEDLINE database search was conducted through February 2017 using the terms 'uveitis' and 'small molecule'. To provide ongoing and future perspectives in treatment options, also clinical trials as registered at ClinicalTrials.gov were included. Both, results from experimental as well as clinical research in this field were included. Since this field is rapidly evolving, a selection of promising agents had to be made. Expert opinion : Small molecules may interfere at different steps of the inflammatory cascade and appear as an interesting option in the treatment algorithm of uveitis. Because of their highly targeted molecular effects and their favorable bioavailability with the potential of topical application small molecules hold great promise. Nevertheless, a careful evaluation of these agents has to be made, since current experience is almost exclusively based on experimental uveitis models and few registered trials.